Contradictions Between Islamic Values and Western Consumerism: Educational Strategies for the Muslim Generation - Hildan Alkautsar; Idzi’ Layyinnati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The phenomenon of consumerism has become a significant challenge for modern Muslim society, especially in the context of increasingly widespread globalization. This research examines the impact of consumerism driven by Western materialism on Islamic identity and principles, as well as the challenges faced by the Muslim generation in balancing contemporary lifestyle demands with Islamic values. Data indicates that 73% of Muslims in urban areas experience difficulties in this regard, exacerbated by the penetration of social media promoting a consumptive lifestyle. The research methodology employs a qualitative approach using literature review methods, involving the collection of data from various written sources to analyze the interaction between Islamic values and consumerism. The findings suggest a crisis of identity, excessive consumptive behavior, and negative impacts on the mental health of the Muslim generation. Therefore, there is a need for the reformulation of Islamic education curriculum that integrates spiritual values, digital economic literacy education based on Sharia principles, and community-based psychological intervention models. It is hoped that this research can contribute to shaping a resilient Muslim generation against the influences of consumerism without losing its Islamic identity.